Activation of canonical Wnt signaling accelerates intramembranous bone regeneration in male mice. Issue 8 (22nd November 2021) - Ko, Frank C.; Moran, Meghan M.; Ross, Ryan D.; Sumner, D. Rick
Abstract: Canonical Wnt signaling plays an important role in skeletal development, homeostasis, and both endochondral and intramembranous repair. While studies have demonstrated that the inhibition of Wnt signaling impairs intramembranous bone regeneration, how its activation affects intramembranous bone regeneration has been underexplored. Therefore, we sought to determine the effects of activation of canonical Wnt signaling on intramembranous bone regeneration by using the well‐established marrow ablation model. We hypothesized that mice with a mutation in the Wnt ligand coreceptor gene Lrp5 would have accelerated intramembranous bone regeneration. Male and female wild‐type and Lrp5‐mutant mice underwent unilateral femoral bone marrow ablation surgery in the right femur at 4 weeks of age. Both the left intact and right operated femurs were assessed at Days 3, 5, 7, 10, and 14. The intact femur of Lrp5 mutant mice of both sexes had higher bone mass than wild‐type littermates, although to a greater degree in males than females. Overall, the regenerated bone volume in Lrp5 mutant male mice was 1.8‐fold higher than that of littermate controls, whereas no changes were observed between female Lrp5 mutant and littermate control mice. In addition, the rate of intramembranous bone regeneration (from Day 3 to Day 7) was higher in Lrp5 mutant male mice compared to their same‐sex littermate controls with no difference in the females. Thus, activation of canonical Wnt signaling increases bone mass in intact bones of both sexes, but accelerates intramembranous bone regeneration following an injury challenge only in male mice.